The Impact of Immigration on the Geographic Mobility of New Zealanders - Steven Stillman; David Mare (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
This paper uses data from the New Zealand Census to examine how the supply of recent migrants in particular skill groups affects the geographic mobility of the New Zealand-born and earlier migrants. We identify the impact of recent migration on mobility using the "area-analysis" approach, which exploits the fact that immigration is spatially concentrated, and thus a change in the local supply of migrants in a particular skill group should have an impact on the mobility of similarly skilled nonmigrants in that local labour market. Overall, our results provide little support for the hypothesis that migrant inflows displace either the NZ-born or earlier migrants with similar skills in the areas that new migrants are settling. If anything, they suggest that there are positive spillovers between recent migrants and other individuals that encourage individuals to move to or remain in the areas in which similarly skilled migrants are settling. Thus, it appears unlikely that internal mobility moderates any potential impacts of immigration on labour or housing markets in New Zealand.
Keywords: J61; R23; 330; Immigration; Mobility; New Zealand; Labour Market Areas